Triazoloquinolines I: Synthetic Methods and Pharmacological Properties of [1,2,3]triazoloquinoline Derivatives - Khidre, Rizk E.; Radini, Ibrahim M.A.; Ameen, Tahah A.; Abdelgawad, Ahmed A.M. (Current Organic Chemistry, 2021)
This review deals with the synthetic methods and pharmacological properties of [1,2,3]triazoloquinoline derivatives. There are ten isomers of fused [1,2,3]triazoloquinoline according to the junction between triazole and quinoline. The synthetic methods are subdivided into groups according to the type of isomers. The pharmacological activity of [1,2,3]triazoloquinoline was also reported.
Keywords: heterocycles